Parameter optimization of fused deposition modeling process for 3d printed prosthetic socket using PCR-TOPSIS method - Lim, Guo Dong (2024)
Prosthetic devices play a crucial role in the rehabilitation process of amputees while socket serves as the most critical component to ensure their success. However, the conventional fabrication process of prosthetic sockets is a labour-intensive and time-consuming process. The advancement of additive manufacturing (AM) in rapid development and its ability to create free-form geometry have posed the potential in revolutionizing traditional manufacturing industries. Fused deposition modeling (FDM) has been the most popular technique in AM technology used in socket fabrication. However, the strength of FDM products is influenced by a series of FDM printing parameters. Therefore, this study aims to investigate the optimum combination of FDM printing parameters in the development of transtibial prosthetic sockets. The study was initiated with the material selection while three FDM materials were investigated and their strength is compared to the conventional socket material, polypropylene (PP). Polylactic acid (PLA) was identified to be the most suitable material due to its highest performance index of 79.74 and has been employed for the subsequent parameter optimization study. A three-dimensional (3D) scanner was utilized to capture the digitized data of the amputee’s stump and convert it into a stereolithography (STL) mesh model. The 3D model of the prosthetic socket was then constructed using the computer-aided-design (CAD) software and tested at different socket thicknesses to determine the appropriate thickness of the socket wall. Subsequently, the samples of the prosthetic sockets were prepared with an FDM printing machine and examined for their structural strength according to the ISO 10328 standard. Experimental data obtained were evaluated and the optimum printing parameter combination was determined through PCR-TOPSIS analysis. The optimum condition to fabricate the 3D printed socket was found to be the combination of 1.0 mm nozzle diameter, 0.48 mm layer thickness, and 30% infill percentage. Additionally, infill percentage is identified to be the most significant printing parameter followed by layer thickness and nozzle diameter.